If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5 + 5x) + -6(7x + 7) = 52 (5 * -2 + 5x * -2) + -6(7x + 7) = 52 (-10 + -10x) + -6(7x + 7) = 52 Reorder the terms: -10 + -10x + -6(7 + 7x) = 52 -10 + -10x + (7 * -6 + 7x * -6) = 52 -10 + -10x + (-42 + -42x) = 52 Reorder the terms: -10 + -42 + -10x + -42x = 52 Combine like terms: -10 + -42 = -52 -52 + -10x + -42x = 52 Combine like terms: -10x + -42x = -52x -52 + -52x = 52 Solving -52 + -52x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '52' to each side of the equation. -52 + 52 + -52x = 52 + 52 Combine like terms: -52 + 52 = 0 0 + -52x = 52 + 52 -52x = 52 + 52 Combine like terms: 52 + 52 = 104 -52x = 104 Divide each side by '-52'. x = -2 Simplifying x = -2
| 9t+q=4t-9 | | 3=y+8 | | 6(r+2)=-12-12r | | 7(6n-9)= | | 9v-5-7=16 | | 30-6x=-3(x-6) | | 9x+31=91 | | 23=8+7(h+2) | | 6y-7=2y+15 | | 2=5p-8 | | -2=6-x+3x | | 2(3y+9)=-16 | | x+y+3=10 | | 4(1-8a)=-22 | | (5x-3)=(4x+12) | | -7+3(1+4b)=-26 | | 15=2m-3+6 | | (3x-1)*(2x^2+4x+3)= | | 5.1x+7.2x=-8.4 | | 11y^2-78y+13=0 | | 3r+2r=27 | | 5x^2+29x+84=0 | | H-(2h-4)=-8 | | 10x+-2=-12 | | 6v-3+6v=-3 | | -31-3d=-6(4d-2) | | 2(3+2x)-4(x+2)=-2 | | 5(4+8a)+7(4a-4)=-76 | | -4x-2y=-5 | | 8x^2-28xy= | | 2x^8-3x^6-x^4-3x^2+2=0 | | 4(a-9)=8a |